Methicillin and Vancomycin Resistant Staphylococcus aureus and Associated Factors from Surgical Ward Inpatients at Debre Markos Referral Hospital, Northwest Ethiopia - Tefera S; Awoke T; Mekonnen D (Infection and Drug Resistance, 2021)
Samrawit Tefera,1,2 Tewachew Awoke,1 Daniel Mekonnen1,3 1Department of Medical Laboratory Sciences, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 2Department of Medical Laboratory, Debre Markos Referral Hospital, Debere Markos, Ethiopia; 3Department of Health Biotechnology, Biotechnology Research Institute, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Daniel MekonnenDepartment of Medical Laboratory Sciences, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaTel +251912990288Email nigusdaniel@gmail.comIntroduction: Staphylococcus aureus is a well-known superbug and leading causes of wound infections. The clinical epidemiology of methicillin resistant S. aureus (MRSA) and vancomycin resistant S. aureus (VRSA) is not well documented in Ethiopia. The aim of this study was to determine the proportion of MRSA, VRSA and associated factors from surgical inpatients in Debre Markos Referral Hospital (DMRH), Northwest Ethiopia.Methods: A facility-based cross-sectional study was conducted from February to April 2020 at DMRH. A structured questionnaire was used to gather demographic and clinical data. Wound swab was collected from inpatients and then inoculated on blood agar and mannitol salt agar. The presence of MRSA and VRSA was determined using the cefoxitin (30 μg) antibiotic disk diffusion and vancomycin E-test methods, respectively. The data were analyzed using SPSS 20. Data were analyzed using bivariate and multivariate logistic regression analysis. A P-value < 0.05 was considered statistically significant.Results: A total of 242 wound cases were enrolled and the majority of them were males 172 (71.1%). Among the total enrolled cases, S. aureus was identified from 71 (29.3%) of the admitted patients. The proportion of MRSA was 32 (13.22%) and that of VRSA was 4.1%. The proportion of vancomycin intermediate S. aureus (VISA) was gauged at 4.5%. Hospital stay over 72 hrs, wound depth, current antibiotic use, and previous history of wound infection showed statistically significant association with MRSA. On the contrary, VRSA did not showed any significant association against the analyzed variables.Conclusion: High proportions of S. aureus isolates became MRSA; resistant to all β-lactam antimicrobial agents excluding newer cephalosporin. In addition, the proportion of VRSA/VISA was also high. Multiple variables demonstrated significant associations with MRSA. Hence, intervention measures for MRSA risk groups must be in place. Furthermore, hospital infection control and an antibiotic stewardship program should be strengthened.Keywords: Nosocomial infection, surgical inpatients, MRSA, VRSA, Debre Markos Referral Hospital, Ethiopia